Early results of micropulse transscleral cyclophotocoagulation for the treatment of glaucoma. Issue 4 (July 2020) - Nguyen, Alexander T; Maslin, Jessica; Noecker, Robert J
Purpose: To describe our clinical experience with the efficacy and safety of micropulse transscleral cyclophotocoagulation as a treatment for glaucoma. Methods: In this retrospective case series, we reviewed the charts of 95 consecutive patients with various glaucoma subtypes who underwent micropulse transscleral cyclophotocoagulation. Patients were offered micropulse transscleral cyclophotocoagulation if they had perimetric glaucoma refractory to intraocular pressure–lowering topical medications and who were poor candidates for traditional filtering surgery. Eligible patients were treated with the Micropulse P3 device (IQ 810 Laser Systems; Iridex, Mountain View, CA, USA) at 2.0–2.5 W for a duration of 90 s per hemisphere at a 31.3% duty cycle. If a retreatment was needed, the power was increased to up to 3.0 W with other parameters remaining the same. Patients were considered successfully treated if their intraocular pressure was lowered by at least 20% compared to their baseline. The main outcome measure was post-operative intraocular pressure; secondary outcome measures included the number of adverse events and complications that occurred with treatment. Results: The glaucoma subtypes treated included primary open-angle glaucoma (n = 51), exfoliation glaucoma (n = 24), chronic angle-closure glaucoma (n = 15), and congenital/juvenile glaucoma (n = 5). The mean pre-operative intraocular pressure was 25.1 ± 5.3 mm Hg and the mean post-operative intraocular pressure at 12 months was 17.5 ± 5.1 mm Hg (p = 0.004). The mean number of intraocular pressure–lowering medications used preoperatively was 3.0 ± 1.1; the mean number of medications used at the 12-month post-operative visit was 1.4 ± 1.0 (p = 0.03). Success with one treatment was achieved in 73 (76.8%) of patients. With multiple treatments, all patients had significant intraocular pressure–lowering compared to baseline. The maximum number of treatments received by any single patient was 5. There were no instances of prolonged intraocular inflammation or long-term hypotony. Conclusion: Micropulse transscleral cyclophotocoagulation appears to be a safe and efficacious treatment for glaucoma. Given its improved safety profile compared to continuous-wave transscleral cyclophotocoagulation, it deserves consideration as a primary procedure.